Memorizing Hijaiyah Letters for Children with Moderate Mental Retardation Using VAKT-Based Media - Rois, Muhammad; Umatin, Choiru; Prameswati, Laudria Nanda; Laili, Ummiy Fauziyah; Rahmawati, Novi Rosita (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This research aims to develop VAKT-based learning media (Visual, Audio, Kinesthetic, Tactile) for hijaiyah letters memorization of children with a moderate level of mental retardation. The research was conducted at Putera Asih Special School (SLB) Kediri. The method used was Research and Development (R&D) combined with the ADDIE model. However, this research only reached the design stage. The data were collected using interviews, observation, and questionnaires. Based on the assessment by media experts, the videos, flashcards, and plasticine developed were very feasible to use, with an average of 90,4%. Also, the material experts stated that the material in the VAKT was very suitable for use at 85%. In addition, the result of the media acceptance questionnaire calculation reached 85%. It means that the VAKT-based learning media was very suitable for use by children with moderate mental retardation to memorize hijaiyah letters at Putera Asih Special School.